The physical action as an experience in the creation process of “The House of the Lame” (The Voz a Vos Bulletin, 2025)
This article seeks to present the results of the systematization process of the play "La casa de los cojos", produced within the University of Caldas, with the support of the Faculty of Arts and Humanities and the Vice-Rector for Research and Postgraduate Studies. The objective of the project was to understand the creative and educational possibilities offered by the exploration of classical dramaturgy through scenic experimentation with Physical Actions. The methodology complements the collective creation from a phenomenological perspective, introducing interviews with the acting team of the creative process. We present a taxonomic approach to the types of Physical Actions experienced by the actors during the creative laboratory process and a general perspective of the experience of the physical action experienced within the tour developed with the show in the “eje cafetero”.
Keywords: physical action; Experience; Movement; Thinking